Andrographolide Loaded in Micro- and Nano-Formulations: Improved Bioavailability, Target-Tissue Distribution, and Efficacy of the "King of Bitters". (February 2019) - Casamonti, Marta; Risaliti, Laura; Vanti, Giulia; Piazzini, Vieri; Bergonzi, Maria Camilla; Bilia, Anna Rita
Abstract: Andrographolide (AG) is the characteristic constituent of Andrographis paniculata, of the Acanthaceae family. This plant is a well-known Asian medicinal plant that is widely used in India, China, and Thailand. A monograph of Herba Andrographidis (Chuanxinlian) is included in the Chinese Pharmacopoeia, which reports that this decoction can "remove heat, counteract toxicity, and reduce swellings." The numerous potential activities of AG range from anti-inflammatory to anti-diabetic action, from neuroprotection to antitumor activity, and from hepatoprotective to anti-obesity properties. However, AG has low bioavailability and poor water solubility, which can limit its distribution and accumulation in the body after administration. In addition, AG is not stable in gastrointestinal alkaline and acidic environments, and has been reported to have a very short half-life. Among the diverse strategies that have been adopted to increase AG water solubility and permeability, the technological approach is the most useful way to develop appropriate delivery systems. This review reports on published studies related to microparticles (MPs) and nanoparticles (NPs) loaded with AG. MPs based on polylactic-glycolic acid (PLGA), alginic acid, and glucan derivatives have been developed for parenteral oral and pulmonary administration, respectively. NPs include vesicles (both liposomes and niosomes); polymeric NPs (based on polyvinyl alcohol, polymerized phenylboronic acid, PLGA, human serum albumin, poly ethylcyanoacrylate, and polymeric micelles); solid lipid NPs; microemulsions and nanoemulsions; gold NPs; nanocrystals; and nanosuspensions. Improved bioavailability, target-tissue distribution, and efficacy of AG loaded in the described drug delivery systems have been reported.